Burnout in the emergency service of a hospital - Sarmiento Valverde, Georgina Silvia (2019)
In order to describe the prevalence of the burnout syndrome in the health personnel working in the emergency area of a public hospital in Cusco, a descriptive cross-sectional analytical study was carried out in 110 workers, among which doctors, nurses, obstetricians and technical personnel were included. We found that 10% of the population suffered from the burnout syndrome. Sixteen point three percent (16.3 %) of the group of physicians, and 8.6 % of the nurses and obstetricians presented signs and symptoms of burnout, and no burnout was found in nurse technicians. Male personnel with temporary contracts who had a service time between 1 to 10 years suffered more frequently from this syndrome. Among the study population, 34.5 % presented a slight-level burnout syndrome, 18.2 % presented a moderate-level burnout syndrome, 15.5 % had high levels of emotional exhaustion, 33.6 % experienced high levels of depersonalization, and finally 51.8 % presented a low personal fulfillment. It is concluded that one out of every ten (10) emergency service workers suffered from the burnout syndrome at the time of the survey, which was greater in doctors and workers with temporary contracts. This situation, which must be corrected, can influence the quality of care in these services.